2019
DOI: 10.1534/g3.119.400541
|View full text |Cite
|
Sign up to set email alerts
|

Expression-Based Cell Lineage Analysis inDrosophilaThrough a Course-Based Research Experience for Early Undergraduates

Abstract: A variety of genetic techniques have been devised to determine cell lineage relationships during tissue development. Some of these systems monitor cell lineages spatially and/or temporally without regard to gene expression by the cells, whereas others correlate gene expression with the lineage under study. The GAL4 Technique for Real-time and Clonal Expression (G-TRACE) system allows for rapid, fluorescent protein-based visualization of both current and past GAL4 expression patterns and is therefore amenable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…In surveying the literature, three studies about genomic CUREs stood out. Olson et al published a genomic CURE designed to screen gene expression in Drosophila [63]. With over 250 co-authors, this study demonstrated significant success in involving a large introductory class size in research-based genomic learning.…”
Section: Undergraduate and Graduate Educationmentioning
confidence: 99%
“…In surveying the literature, three studies about genomic CUREs stood out. Olson et al published a genomic CURE designed to screen gene expression in Drosophila [63]. With over 250 co-authors, this study demonstrated significant success in involving a large introductory class size in research-based genomic learning.…”
Section: Undergraduate and Graduate Educationmentioning
confidence: 99%
“…The Undergraduate Research Consortium for Functional Genomics (URCFG) was established at UCLA in 2003 as an entity representing the collaborative research effort of undergraduates, typically first- and second-year students, participating in a discovery-based laboratory course called Biomedical Research 10H (formerly Life Sciences 10H ). Since that time, the URCFG has conducted several large-scale genetic research projects that have yielded publishable data and research resources ( Chen et al 2005 ; Liao et al 2006 ; Call et al 2007 ; Evans et al 2009 ; Olson et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila has three defined terminally differentiated blood cell types called plasmatocytes, crystal cells, and lamellocytes ( Evans et al 2014 ; Olson et al 2019 ). Plasmatocytes are professional phagocytes, similar to human macrophages and neutrophils, and are by far the most prevalent blood cell type (∼95%) produced.…”
Section: Introductionmentioning
confidence: 99%
“…Though undergraduate scientists have been a staple of Drosophila research groups since Alfred Sturtevant worked for Morgan, only relatively recently has this research been extended to the classroom. Multi-year projects in lab courses at the University of California, Los Angeles identified mutations responsible for eye development ( Call et al 2007 ) and cell lineage analysis ( Olson et al 2019 ) and a multi-year, multi-University consortium directed from Washington University in St. Louis had over 900 undergraduate students finish and annotate the dot chromosomes of a number of Drosophila species ( Leung et al 2015 ). Other C ourse-based U ndergraduate R esearch E xperiences (CUREs) have gained more prominence at Universities as faculty identify the advantages of such an approach ( Shaffer et al 2014 ) (see CUREnet: curenet.cns.utexas.edu for additional information), and using genetic complementation to characterize mutants derived from a screen has been quite successful ( Bieser et al 2019 ; Stamm et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%